Standards for the nursing care of the frail aged - L.R. Uys; B.N. Hunt (AOSIS, 1990)
In this project standards for the nursing care of the institutional care of the frail aged were formulated and then validated by groups of nurses. An instrument was then designed to measure to what extent these standards are reached. The instrument was then tested for reliability and validity in a sample o f 12 institutions in the Eastern Cape and Natal.